Non-alcoholic fatty liver disease and lipotoxicity - Wasilewska, Natalia; Lebensztejn, Dariusz (Clinical and Experimental Hepatology, 2021)
Non-alcoholic fatty liver disease (NAFLD) has become the most common liver pathology worldwide due to the rising prevalence of obesity. This term includes changes from simple steatosis to steatohepatitis and fibrosis. It was previously thought to be a hepatic manifestation of metabolic syndrome, but recent literature describes this relation as much more complex and bi-directional. Development of NAFLD is associated with other metabolic syndrome components but it can also exacerbate insulin resistance and increase cardiovascular risk. Recently a lot of attention is brought to the role of lipids and lipotoxicity in pathogenesis and progression of non-alcoholic fatty disease. It seems that some lipid classes can be protective against liver injury while others are harmful in excessive amounts. This study presents an overview of the main lipids involved in the pathogenesis of non-alcoholic fatty liver disease and summarizes their association with lipotoxicity, insulin resistance, oxidative stress and other processes responsible for its progression.